Phagocytosis of Aspergillus fumigatus by Human Bronchial Epithelial Cells Is Mediated by the Arp2/3 Complex and WIPF2 - Culibrk, Luka; Croft, Carys A.; Toor, Amreen; Yang, S. Jasemine; Singhera, Gurpreet K.; Dorscheid, Delbert R.; Moore, Margo M.; Tebbutt, Scott J. (Frontiers in Cellular and Infection Microbiology, 2019)
Aspergillus fumigatus is an opportunistic fungal pathogen capable of causing severe infection in humans. One of the limitations in our understanding of how A. fumigatus causes infection concerns the initial stages of infection, notably the initial interaction between inhaled spores or conidia and the human airway. Using publicly-available datasets, we identified the Arp2/3 complex and the WAS-Interacting Protein Family Member 2 WIPF2 gene as being potentially responsible for internalization of conidia by airway epithelial cells. Using a cell culture model, we demonstrate that RNAi-mediated knockdown of WIPF2 significantly reduces internalization of conidia into airway epithelial cells. Furthermore, we demonstrate that inhibition of Arp2/3 by a small molecule inhibitor causes similar effects. Using super-resolution fluorescence microscopy, we demonstrate that WIPF2 is transiently localized to the site of bound conidia. Overall, we demonstrate the active role of the Arp2/3 complex and WIPF2 in mediating the internalization of A. fumigatus conidia into human airway epithelial cells.